Flexible Deadlines Impact Student Mental Health and Course Engagement: a Mixed Methods Exploratory Study - Lesley Zannella; Jessica Sutherland (Journal of the Scholarship of Teaching and Learning, 2025)
With the growing number of students at colleges and universities who are considered nontraditional, creating an equitable classroom characterized by Universal Design for Learning has become increasingly important in higher education. In this mixed methods exploratory study, we assess the impact of implementing flexible deadline policies into our courses on students’ learning experience. Across four academic terms, both at the undergraduate and graduate level, at two universities in Canada and the United States, we found that offering students (N = 234) the opportunity to redeem extension coupons resulted in a positive learning experience. Two key themes in our study demonstrate that the extension coupons improved students’ mental health and their level of course engagement. Our study presents implications for teaching practices and policies and provides educators with one way to increase equity in the classroom.